Evaluation of five housekeeping genes for genotyping southern African Ehrlichia ruminantium strains - Morar-Leather, Darshana (University of Pretoria, 2024)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2024.